Combustion engine applications of waste tyre pyrolytic oil. (July 2021) - Mikulski, Maciej; Ambrosewicz-Walacik, Marta; Hunicz, Jacek; Nitkiewicz, Szymon
Abstract: There is abundant worldwide research into combustion engine applications for tyre pyrolysis oil (TPO). However, many of these studies demonstrate conflicting or ambiguous results, so although the huge number of used tyres promises good availability for TPO, its role as fuel for transport applications is still uncertain. This review´s goal is to clarify the case for TPO as transport fuel by means of a critical, wide-ranging and updated review of TPO's engine applications. The work gathers, collates and analyses the results of over 200 influential original research papers, aiming to answer the governing research questions related to TPO production and quality, post-processing and quality improvement and its final end-use engine validation. The work re-evaluates the environmental aspects of TPO technology, setting it against the latest backdrop of growing climate change concern and the urgency to find alternative fuels. The hard economics of TPO are also addressed, for example, assessing other end-of-life tyre management routes and competing fuel alternatives. The critical discussion on the key issues, including the most relevant drivers and boundaries, points towards TPO's use as a fuel component in marine, off-road and heavy-duty road applications. The results indicate that state-of-the-art production methods yield fuel that could be used directly in bunkering chains for marine transport as low-sulphur fuel oil. Discussion reveals that automotive applications are limited to blends not exceeding 10% tyre pyrolytic oil: sulphur and polyaromatic hydrocarbons contents and particulate emissions are the main constraints. Pyrolysis process efficiency is high and feedstock for TPO is both available and flexible. Waste tyre-derived pyrolytic oils could function as a supplementary solution to biofuels, blended to take advantage of their complementary properties. The particular added value of this review is that it bridges the latest knowledge from several domains related to TPO fuel: industrial management, process chemistry, fuel science and combustion/engine research. The resultant analysis is expressed in terms that are accessible to all those domains. It underlines how studies from an individual domain perspective fail to produce the holistic view. The review creates a route towards modern multidisciplinary research supporting TPO´s role in global transition to circular economy.